Needs Analysis in Developing “English for Tour Guides” Materials for High School Students in Kepulauan Seribu, Indonesia - Araminta, Lavinia D.W; Halimi, Sisilia S (UI Scholars Hub, 2020)
Kepulauan Seribu is one of the fastest growing tourism regions in Indonesia, but its growth can be hindered by the lack of English skills of local tour guides. In response to this, a workshop entitled “English for Tour Guides” was conducted for high school students on Pramuka Island, and in-house materials were developed. To determine how the materials were to be designed, a needs analysis using a three-question open-ended questionnaire was carried out in order to identify the students’ views on local tourism, motivation to join the workshop, and aspirations after graduation. The results show that the students considered developing local tourism and improving their English skills, either for achieving future personal purposes or interacting with foreign visitors, important. Furthermore, this study also found that their motivation had both integrative and instrumental orientations. Based on the needs analysis, a set of principles informed by the literature on language teaching and learning was chosen, and it directed the pedagogical tasks selected as part of the materials.